Mesoporous silica nanoparticles for (19)F magnetic resonance imaging, fluorescence imaging, and drug delivery - Nakamura, Tatsuya (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
Multifunctional mesoporous silica nanoparticles (MSNs) are good candidates for multimodal applications in drug delivery, bioimaging, and cell targeting. In particular, controlled release of drugs from MSN pores constitutes one of the superior features of MSNs. In this study, a novel drug delivery carrier based on MSNs, which encapsulated highly sensitive (19)F magnetic resonance imaging (MRI) contrast agents inside MSNs, was developed. The nanoparticles were labeled with fluorescent dyes and functionalized with small molecule-based ligands for active targeting. This drug delivery system facilitated the monitoring of the biodistribution of the drug carrier by dual modal imaging (NIR/(19)F MRI). Furthermore, we demonstrated targeted drug delivery and cellular imaging by the conjugation of nanoparticles with folic acid. An anticancer drug (doxorubicin, DOX) was loaded in the pores of folate-functionalized MSNs for intracellular drug delivery. The release rates of DOX from the nanoparticles increased under acidic conditions, and were favorable for controlled drug release to cancer cells. Our results suggested that MSNs may serve as promising (19)F MRI-traceable drug carriers for application in cancer therapy and bio-imaging.